The Cerebrospinal Fluid in Multiple Sclerosis - Deisenhammer, Florian; Zetterberg, Henrik; Fitzner, Brit; Zettl, Uwe K. (Frontiers in Immunology, 2019)
Investigation of cerebrospinal fluid (CSF) in the diagnostic work-up in suspected multiple sclerosis (MS) patients has regained attention in the latest version of the diagnostic criteria due to its good diagnostic accuracy and increasing issues with misdiagnosis of MS based on overinterpretation of neuroimaging results. The hallmark of MS-specific changes in CSF is the detection of oligoclonal bands which occur in the vast majority of MS patients. Lack of oligoclonal bands (OCB) has a very high negative predictive value indicating a red flag during the diagnostic work-up and alternative diagnoses should be considered in such patients. Additional molecules of CSF can help to support the diagnosis of MS, improve the differential diagnosis of MS subtypes and predict the course of the disease, thus selecting the optimal therapy for each patient